Integrating cultural heritage into biology learning through an animated video on Borobudur Temple - Eka Lestari; Shefa Dwijayanti Ramadani; Karunia Galih Permadani (Research and Development in Education (RaDEn), 2025)
The integration of local potential into the learning process can significantly enhance students’ conceptual understanding and contextual relevance of the subject matter. However, biology education on the topic of Animalia at State Senior High School 3 Magelang lacks sufficient media resources, leading to suboptimal learning outcomes. There is a need to integrate learning media with the local potential of the Borobudur Temple. This research aims to develop an animated video illustrating the diversity of Animalia, inspired by the Gandawyuha relief in the third hallway wall of Borobudur Temple, and to assess its effectiveness as a learning tool. The development follows the ADDIE model, with video feasibility analyzed through expert validation assessments and user feedback. Validation results indicated that the animation video received a “very valid” rating from media and subject matter experts, with 95% and 86% percentages. The feasibility assessment based on responses from the biology teacher and students yielded scores of 96% and 90%, reflecting “very valid” and “very good” criteria. The results demonstrate that the animated video developed is an interesting learning media.